Determinants of Student Personal Financial Management: Literacy, Lifestyle, and Self-Efficacy - Bilal Sandra; Rike Setiawati; Besse Wediawati (Universitas Darwan Ali, 2026)
Generation Z, particularly university students, is currently navigating a vortex of complex financial challenges driven by exposure to consumptive lifestyles, impulsive shopping behaviors, and fundamental difficulties in maintaining disciplined monthly budgets. This phenomenon underscores the urgency of analyzing the influence of financial literacy, lifestyle, and self-efficacy on the personal financial management of 2022 Management Program students at Universitas Jambi. Utilizing a quantitative method and a purposive sampling technique with 136 respondents, this research processed data through the Partial Least Square (PLS) approach using SmartPLS 4.0. The analysis yields compelling findings: lifestyle and self-efficacy exert a positive and significant influence on personal financial management, whereas financial literacy shows a positive but insignificant effect. These results reveal that theoretical financial knowledge is not an absolute guarantee of prudent financial management. Consequently, this study asserts that to build optimal financial behavior, students must go beyond theoretical insights by cultivating psychological resilience through strong self-efficacy and disciplined lifestyle control amidst the currents of modern consumerism